Análise do comportamento de rebolos convencionais na retificação de aços frágeis e dúcteis - Bianchi, Eduardo Carlos [UNESP]; Fernandes, Odilson Coimbra [UNESP]; Mogami, Octávio [UNESP]; Da Silva Jr., Carlos Elias [UNESP]; De Domenico Valarelli, Ivan [UNESP]; Aguiar, Paulo Roberto (My University, 1997)
The aim of this work war to study the behavior of the plan tangential grinding process with conventional grinding wheels, under several machining conditions and a selected dressing condition. The analysis of the grinding performance was done regarding the cutting surface wear behavior of the grinding wheel for brittle and ductile steels workpieces. The grinding input parameters, which were, cutting speed, workpiece speed and cutting feed, were chosen based on the grinding machine characteristics. The results discussion emphasized the wear mechanism of the grinding wheel cutting surface and the cutting phenomenology of the grinding process.
Behavior analysis of conventional grinding wheel in brittle and ductile steels machining
Keywords: Conventional Grinding Wheels; Grinding Wheel Wear; Machining Conditions; Grinding wheels; Steel; Wear of materials; Brittle steel; Ductile steel; Grinding (machining)